2013
DOI: 10.2478/amm-2013-0031
|View full text |Cite
|
Sign up to set email alerts
|

Shear Strength and Dsc Analysis of High-Temperature Solders

Abstract: The work is devoted to the study of shear strength of soldered joints fabricated by use of high-temperature solders of types Bi-11Ag, Au-20Sn, Sn-5Sb, Zn-4Al, Pb-5Sn, and Pb-10Sn. The shear strength was determined on metallic substrates made of Cu, Ni, and Ag. The strength of joints fabricated by use of flux and that of joints fabricated by use of ultrasonic activation without flux was compared. The obtained results have shown that in case of soldering by use of ultrasound (UT), higher shear strength of solder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Another reason is the solid solution hardening effect of Sb. Some studies have found that when Sb is added to SAC alloy, Sb can have a solid solution hardening effect in the β-Sn matrix phase [ 31 , 32 ]. After adding Sb, more Ag 3 (Sn, Sb) and Cu 6 (Sn, Sb) 5 particles precipitated on the Cu 6 Sn 5 layer, and the grain hardening effect occurred [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another reason is the solid solution hardening effect of Sb. Some studies have found that when Sb is added to SAC alloy, Sb can have a solid solution hardening effect in the β-Sn matrix phase [ 31 , 32 ]. After adding Sb, more Ag 3 (Sn, Sb) and Cu 6 (Sn, Sb) 5 particles precipitated on the Cu 6 Sn 5 layer, and the grain hardening effect occurred [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…These competitive strategies focus primarily on customer groups. However, these strategies may focus on competitor activities and proactive seekers of foreign expansion (Koleňák, Koleňáková, 2012).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Reactions on the boundary of Bi-solders and metallic substrates were studied in works [15][16][17][18][19]. Examples of another solders are in the following studies [20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%